Atypical clinical presentation and successful treatment with oral cholic acid of a child with defective bile acid synthesis due to a novel mutation in the HSD3B7 gene - Grazia Bossi; Giuseppe Giordano; Gaetana Anna Rispoli; Giuseppe Maggiore; Mauro Naturale; Daniela Marchetti; Maria Iascone (Pediatric Reports, 2017)
We report definitive diagnosis and effective treatment with oral cholic acid in one Italian male child affected by 3β- hydroxy-Δ5-C27-steroid dehydrogenase (3β- HSD) deficiency. He presented with failure to thrive, hepatomegaly and multiple cystic images in kidneys; no biochemical evidence of cholestasis. Large amounts of bile acid metabolites was detected in urine by fast atom bombardment ionization mass spectrometry (FAB-MS). HSDH3B7 gene analysis identified one mutation in intron 4, at nucleotide 432, G>A substitution that has never been reported before.The replacement therapy with oral cholic acid started early after the diagnosis and is still ongoing. Three years later hepatomegaly is no longer evident, liver function is normal and the child is growing regularly. In our experience, clinical features of 3β-HSD deficiency can be very poor and even cholestasis can lack at diagnosis. Early replacement therapy with cholic acid is safe and leads to clinical and biochemical control of the disease.